Pembinaan dan Pendampingan (Coaching) Pembuatan Laporan Keuangan Akuntansi Sederhana Pada UMKM Industri Kreatif Fashion - Kurniawati, Susilaningtyas B; Supartini; Maryanti, Istinganah Eni; Abdullah, Syahriar (Program Studi Pendidikan Kimia FKIP Universitas Mataram, 2025)
The fashion industry is the largest contributor to exports from the creative economy. One creative fashion industry that still has promising market opportunities is the t-shirt production business. However, micro, small, and medium enterprises (MSMEs) that produce t-shirts often experience difficulties in developing their businesses for the long term (sustainability). This occurs because t-shirt business owners often make financial decision-making errors due to a lack of knowledge about proper financial reporting management, starting from recording accounting reports, managing cash flow, calculating profits and losses, to developing appropriate business plans. This community service activity on this occasion focused on t-shirt business partners who had never received socialization or coaching and mentoring in terms of implementing good financial management accounting knowledge. The main objective of the Coaching and Mentoring (coaching) for these digital-based creative industry business owners was to identify problems in recording accounting reports and provide solutions to existing problems. The results of this community service activity were that digital-based creative industry business owners who previously lacked knowledge of the basics of accounting became aware of and able to create simple reports (balance sheets and profit and loss) and use computerized technology to record transactions and prepare financial reports automatically.